Penerapan Model Pembelajaran Direct Instruction Untuk Meningkatkan Motivasi Berprestasi Siswa Kelas X Multimedia di SMK Ketintang Surabaya - Ayu Pusparini; Mochamad Cholik; Tri Rijanto; Ekohariadi; I.G.P Asto Budi Tjahjanto; Marniati (Jayapangus Press, 2023)
The learning models becomes an important tool in the learning process. The abilities that students are expected to have will be determined by using appropriate learning models. The study aims to determine how the application of direct instruction and e-learning learning models in basic programming subjects can increase achievement motivation. This research used Quasi-Experiment approach. The design used anon-euivalent control group. The number of research samples consisted of 70 students of class X MM SMK Ketintang Surabaya. The independent variable in this studies was application of direct instruction (X1), E-learning (X2) while the dependent variable used is achievement motivation (Y). Multiple regression used for analyze data. The results showed that tcount = 5.5924 and ttable = 1.371 for dk = 5, at significant level 5%. Test criteria show that tstatistic> ttable (4.5924 > 5.371) then H0 rejected, meaning H1 accepted. It can be interpreted that difference between the Direct Instruction learning model and e-learning is significant.